2020
DOI: 10.1037/ort0000451
|View full text |Cite
|
Sign up to set email alerts
|

Family social support buffers the intergenerational association of maternal adverse childhood experiences and preschoolers’ externalizing behavior.

Abstract: Despite previous work demonstrating that an accumulation of maternal adverse childhood experiences (ACEs) is associated with negative health outcomes across generations, few studies have investigated protective factors beyond the parent–child dyad in the intergenerational transmission of adversity. The current study extends previous findings by examining maternal family social support as a culturally relevant buffer in the association between mothers’ ACEs and her children’s behavior problems in early childhoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 112 publications
0
38
2
Order By: Relevance
“…Interdisciplinary interest in the intergenerational sequelae of early adversity and trauma is on the rise. In the last few years, some studies have demonstrated that a mother’s ACEs history is connected to her child’s risk of social-emotional problems, including externalizing symptoms such as aggression and hyperactivity and internalizing symptoms such as anxiety and depression (Cooke et al, 2019; Doi et al, 2020; Fredland et al, 2018; Hatch et al, 2020; Letourneau et al, 2019; McDonald et al, 2019; Rieder et al, 2019; Sun et al, 2017). Less is known, however, about the processes through which these effects emerge.…”
Section: Research Synthesismentioning
confidence: 99%
“…Interdisciplinary interest in the intergenerational sequelae of early adversity and trauma is on the rise. In the last few years, some studies have demonstrated that a mother’s ACEs history is connected to her child’s risk of social-emotional problems, including externalizing symptoms such as aggression and hyperactivity and internalizing symptoms such as anxiety and depression (Cooke et al, 2019; Doi et al, 2020; Fredland et al, 2018; Hatch et al, 2020; Letourneau et al, 2019; McDonald et al, 2019; Rieder et al, 2019; Sun et al, 2017). Less is known, however, about the processes through which these effects emerge.…”
Section: Research Synthesismentioning
confidence: 99%
“…The FRI program aims to provide holistic, trauma-informed care while addressing social and mental wellness. Many studies have been conducted on the health outcomes and the intergenerational effects of maternal ACEs on the child, 2 , 12 , 13 but few studies have examined protective factors beyond the parent-child dyad. These protective factors are what the FRI program seeks to employ and study through the interventions provided by a multidisciplinary team.…”
Section: Discussionmentioning
confidence: 99%
“…ACEs on the child,2,12,13 but few studies have examined protective factors beyond the parentchild dyad. These protective factors are what the FRI program seeks to employ and study through the interventions provided by a multidisciplinary team.…”
mentioning
confidence: 99%
“…For example, Conn et al (2018) found parents emphasizing the importance of providers taking time to introduce the ACEs questionnaire. In relation to assessment of parent ACEs, the impact of parent ACEs on child well-being has been demonstrated in research (Folger et al, 2018; Hatch et al, 2020; Schickedanz et al, 2018), and several other projects have implemented programs to assess parent ACEs (Kia-Keating et al, 2019; McCrae & Burkhardt, 2020). Going forward, it will be important for routine inquiry programs in primary care to take this into consideration.…”
Section: Discussionmentioning
confidence: 99%